(untitled) (World Science, 2018)
The paper considers biotechnological characteristics of new breeds of mulberry silkworm „V-1“ and „V-2“, which are relatively resistant to the worm disease „nuclear polyhedrosis“. The hybreeds were obtained from mulberry silkworm breeds „Dighmuri“ and „Iveria“. Breed “Iveria” is characterized by short period of feeding; it was created for the west Georgia zone, while the cocoon thread length of the breed “Dighmuri” is 1800-2000 meter, silk capacity of live cocoon is 25-26%, but these breeds are characterized by relatively low viability [1,2,3]. Our research aimed to improve namely this flaw. As a result of complex selection works carried out for the improvement of the above stated viability and other major indices we received new highly productive breeds, which by their indices equal or exceed initial breeds.